Enhancing Micro and Small Enterprise Competitiveness through Integrated Enterpreneurship Education and Digital Literacy - Ratu Eva Febriani; Benardin Bernadin; Hutapia Hutapia; Izharudin Izharudin (Universitas Putra Indonesia YPTK Padang, 2026)
Micro and Small Enterprises (MSEs) play a vital role in promoting rural economic development; however, many business owners continue to face challenges related to entrepreneurial competencies and digital technology adoption. This community service program aimed to enhance the competitiveness of MSE owners in Sri Kuncoro Village through an Integrated Entrepreneurship Education and Digital Literacy (IEEDL) model. The program adopted a Participatory Action Learning approach involving 25 MSE owners and was implemented through four stages: needs assessment, integrated training, business mentoring, and program evaluation. Program effectiveness was assessed using pre-test and post-test instruments, participant observations, and satisfaction questionnaires. The results demonstrated substantial improvements in participants' competencies in business planning, financial management, digital literacy, and digital marketing, with the highest gain observed in marketplace utilization. Participants also reported a high level of satisfaction with the training, while observation findings indicated active engagement throughout the learning activities. The integration of entrepreneurship education with practical digital literacy training, supported by continuous mentoring, proved effective in facilitating the adoption of digital business practices among rural entrepreneurs. This program contributes by introducing the Integrated Entrepreneurship Education and Digital Literacy (IEEDL) model as a practical and replicable framework for strengthening the competitiveness of rural MSEs and supporting sustainable local economic development.